047 Multiple sclerosis patient perspectives: disease education and communication needs. Issue 6 (27th May 2022) - O'Neill, Jessica; Ayer, Mavis; Colhoun, Samantha; Daykin, Nicola; Hamill, Brenda; Gabriele, Simone; Florio, Jordanne; Pulcini, Serena; Thomson, Alison
Abstract : MS is a progressive disease that significantly impacts quality-of-life (QoL).This study aimed to identify unmet disease education and communication needs in people with MS (pwMS) to empower informed decisions, enable self-management and to maintain independence for as long as possible. A Steering Group of MS nurses and patient representatives formed and two studies for pwMS were co-developed: a qualitative Online Patient Community activity (using Ipsos' Syndicated MS Online Patient Community) and a quantitative online survey (via the MS Trust). Data were analyzed from 28 and 117 respondents with relapsing remitting MS (RRMS), from the Ipsos' Syndicated MS Online Patient Community and quantitative survey, respectively. Data from the quantitative survey revealed: 50% reported knowing a 'great deal' or a 'fair amount' about disability progression. Maintaining independence was a key goal for pwMS, however only 33% reported they felt that they could 'plan for the long term', and 21% said they set goals for managing their MS. Data from this study will explore the relationship between perceived knowledge, planning for the future, and impact on QoL. This study highlights the importance of understanding unmet needs in education, linking disease progression and impact on future QoL in pwMS. Acknowledgements: This project was sponsored by Roche Products Ltd. Ipsos MORI UK Ltd provided support in developing and conducting the surveys and performing data analysis, which was funded by Roche Products Ltd. jessica.oneill.jo1@roche.com